2016
DOI: 10.1016/j.cct.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

An exercise trial to reduce cancer related fatigue in African American breast cancer patients undergoing radiation therapy: Design, rationale, and methods

Abstract: Background-Cancer related fatigue (CRF) is a common and debilitating side-effect of radiotherapy in breast cancer patients. Physical activity interventions can attenuate CRF but evidence in African-American women with breast cancer is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Thus, the combined results of the increase of the lower body strength and endurance shown in the 30 s chair stand test could explain the reduced levels of perceived fatigue observed in the lymphoma patients [2,7]. In this regard, we have given lymphoma patients the opportunity to improve their quality of life, as demonstrated by previous studies [12,13,14,15], and to understand the importance of the physical activity as a major prevention tool [29,30].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Thus, the combined results of the increase of the lower body strength and endurance shown in the 30 s chair stand test could explain the reduced levels of perceived fatigue observed in the lymphoma patients [2,7]. In this regard, we have given lymphoma patients the opportunity to improve their quality of life, as demonstrated by previous studies [12,13,14,15], and to understand the importance of the physical activity as a major prevention tool [29,30].…”
Section: Discussionmentioning
confidence: 72%
“…This study’s results are in agreement with several other studies that showed the benefits of combined aerobic and strength training in cancer patients and survivors, reporting improvements in functional fitness levels and psychological well-being [21,22,23,24,25,26,27]. Many studies demonstrated that exercise performed both during and after treatment is an effective tool to achieve health benefits in terms of functional performance, fatigue, psychological wellbeing, and health-related quality of life in cancer patients and survivors [7,12,13,14,15,46,47]. However, it is known that the benefits of physical exercise may vary according to the type of cancer and treatment, and the current lifestyle of the patient [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of cancer, fatigue is defined as a distressing, persistent, subjective sense of physical, emotional, and/or cognitive tiredness or exhaustion related to cancer or cancer treatment that is not proportional to recent activity and interferes with usual functioning ( Berger et al, 2010 ). Fatigue in patients with cancer is also described as a common and debilitating burden ( Dash et al, 2016 ). Depending on the measures used and the cancer stages, the prevalence of fatigue in patients with cancer ranges from 60 to 99% ( Lawrence et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%